A branch-and-price algorithm for production routing problems with carbon cap-and-trade. (April 2017) - Qiu, Yuzhuo; Qiao, Jun; Pardalos, Panos M.
Abstract: This study presents a model for a pollution production-routing problem under carbon cap-and-trade. The aim is to incorporate carbon emissions into production inventory and routing decisions. The model is characterized by an additional flow-related cost structure, which generalizes models for pollution-routing problems and production inventory and routing problems. Correspondingly, we develop a branch-and-price heuristic by incorporating a column-generation formulation based on the Dantzig–Wolfe decomposition. In addition, we design an ad hoc label-setting algorithm to deal with time-slice networks in pricing subproblems. Computational results allow us to provide managerial insights concerning reduction of carbon emissions in supply chains. We prove that the model has the potential to reduce emission levels of carbon dioxide and operational costs. Abstract : Highlights: MILP models for pollution production routing problems with carbon cap-and-trade. Branch-and-price heuristic based on Dantzig–Wolfe decomposition and column generation. Ad hoc label-setting algorithm for pricing subproblem of branch-and-price heuristic. Insights on sensitivity of integrated supply chain operations to carbon regulation. Insights on balance of lost sale, transportation, horizon with emission reduction.